Managing portfolio risk in strategic technology management: evidence from a panel data-set of the world's largest R&D performers. Issue 7 (2nd October 2016) - Neuhäusler, Peter; Schubert, Torben; Frietsch, Rainer; Blind, Knut
ABSTRACT: In this article, we analyze the impact of firms' technology bases on their financial performance. By taking a strategic perspective of technology, we argue that it is not sufficient to analyze only the size or novelty/quality of the technology base as technology bases can best be understood as portfolios of individual technologies. In such a framework, risk consideration should be taken into account. More specifically, we argue that increasing technological breadth can serve as a hedge against the inherent uncertainties of developing and commercializing technology, in particular when the technology base is very large or novel. We also propose that technology has higher impacts on financial performance for firms with broader technology portfolios. A similar argument proposes that technological breadth can offset the increased risks of addressing foreign markets. We test our hypotheses using an international panel data-set of large R&D-performing firms. Our results suggest that broad technology portfolios can indeed serve as a hedge against technological and commercialization risks.